Film Flow Field Analysis of Hydrodynamic Polishing Based on FLUENT (Journal of Fiber Bioengineering and Informatics, 2015)
The characteristics of film flow field have important effects on the quality of hydrodynamic polishing.Oriented preparation requirements of amorphous film substrate, in order to further study the floatingheight of hydrodynamic polishing base plate in working conditions, the mathematical model is establishedand the theoretical analysis has been carried out for the wedge hydrodynamic floating polishing baseplate. The relationship between buoyancy and floating height is researched. The floating height iscalculated under the known loads, and then the pressure distribution along the circumferential directionof base plate is analyzed. Film flow field is simulated and analyzed using the FLUENT based on thecalculated floating height. It indicts that the bearing capacity of wedge combination plane decreaseswith the increase of floating height, and the downward trend slows down gradually. The pressure peakdistributes near the interface of wedge flow field and parallel flow field. Through the pressure distributioncomparison of simulation and calculation, the correctness of the mathematical model and simulationmethod is verified.